If the integral as written in my comment is accurate, then we have
![I=\displaystyle\int_(3/2)^2√((x-1)(3-x))\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/7fiy1fh35kfe5ko7guqguvvn6yunxixex6.png)
Expand the polynomial, then complete the square within the square root:
![(x-1)(3-x)=-x^2+4x-3=1-(x-2)^2](https://img.qammunity.org/2021/formulas/mathematics/college/n5aw6d8pyazxeqcdj81cnutdxrbt8acnfn.png)
![I=\displaystyle\int_(3/2)^2√(1-(x-2)^2)\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/uvd0cfy8liuc0zf5suhiw2lr4bqh5xegvy.png)
Let
and
:
![I=\displaystyle\int_(\pi/3)^(\pi/2)√(1-(2-\cos\theta-2)^2)\sin\theta\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/szg2s7groy106pbv444ua0wyf8aetc3kbe.png)
![I=\displaystyle\int_(\pi/3)^(\pi/2)√(1-\cos^2\theta)\sin\theta\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/6tvx7p6mhy2hi4u6gto0qh9twvz6imb4qt.png)
![I=\displaystyle\int_(\pi/3)^(\pi/2)√(\sin^2\theta)\sin\theta\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/je6dk2ble45y9vtonn3yziyswsd481dsuq.png)
Recall that
for all
, but for all
in the integration interval we have
. So
:
![I=\displaystyle\int_(\pi/3)^(\pi/2)\sin^2\theta\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/kflr307t470kzgiw7cl13r8gl1xxs6ur5r.png)
Recall the double angle identity,
![\sin^2\theta=\frac{1-\cos(2\theta)}2](https://img.qammunity.org/2021/formulas/mathematics/college/t0folbj2papsbi5c0jz4rq8w4bp5o0qp24.png)
![I=\displaystyle\frac12\int_(\pi/3)^(\pi/2)(1-\cos(2\theta))\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/4f07bwu5da0ul0ofciywrt9bmdw61ma9o6.png)
![I=\frac\theta2-\frac{\sin(2\theta)}4\bigg|_(\pi/3)^(\pi/2)](https://img.qammunity.org/2021/formulas/mathematics/college/betvrcff2secik3foc1s77vysy08blcc5j.png)
![I=\frac\pi4-\left(\frac\pi6-\frac{\sqrt3}8\right)=\boxed{\frac\pi{12}+\frac{\sqrt3}8}](https://img.qammunity.org/2021/formulas/mathematics/college/muams11r1vgtt2kn78694eb2is7np3kvn1.png)
You can determine the more general result in the same way.
![I=\displaystyle\int_p^q√((x-a)(b-x))\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/ttax12dlc9hgdk8md8ze1yj702cxs1esrw.png)
Complete the square to get
![(x-a)(b-x)=-(x-a)(x-b)=-x^2+(a+b)x-ab=\frac{(a+b)^2}4-ab-\left(x-\frac{a+b}2\right)^2](https://img.qammunity.org/2021/formulas/mathematics/college/41rtlwlkq754ptytog7zateznx7xzskwv4.png)
and let
for brevity. Note that
![c=\frac{(a+b)^2}4-ab=\frac{a^2-2ab+b^2}4=\frac{(a-b)^2}4](https://img.qammunity.org/2021/formulas/mathematics/college/pb2dfyyujk2d3ztrbiy0hkljiyj9e0avjr.png)
![I=\displaystyle\int_p^q\sqrt{c-\left(x-\frac{a+b}2\right)^2}\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/j4scfs0o18zdq062ovbjqsybo3bqqk2dz6.png)
Make the following substitution,
![x=\frac{a+b}2-\sqrt c\,\cos\theta](https://img.qammunity.org/2021/formulas/mathematics/college/lqnt6l8h8qwesw4of7ew0ejqdyox25a52v.png)
![\mathrm dx=\sqrt c\,\sin\theta\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/ylz6vctefmw3nrqrbirtnq7jb1gkv57125.png)
and the integral reduces like before to
![I=\displaystyle\int_P^Q√(c-c\cos^2\theta)\,\sin\theta\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/6ac1an988aasy3hhfejklzpse3rwzwprs8.png)
where
![p=\frac{a+b}2-\sqrt c\,\cos P\implies P=\cos^(-1)\frac{\frac{a+b}2-p}{\sqrt c}](https://img.qammunity.org/2021/formulas/mathematics/college/usisx0mzj1t994y7rsyrl15mdpao67jap2.png)
![q=\frac{a+b}2-\sqrt c\,\cos Q\implies Q=\cos^(-1)\frac{\frac{a+b}2-q}{\sqrt c}](https://img.qammunity.org/2021/formulas/mathematics/college/qzyq99catw2xkdv41bkaxysgvxtbs599of.png)
![I=\displaystyle\frac{\sqrt c}2\int_P^Q(1-\cos(2\theta))\,\mathrm d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/gd8x91f7rw7fg9u2w3eigldqdkghswa7er.png)
(Depending on the interval [p, q] and thus [P, Q], the square root of cosine squared may not always reduce to sine.)
Resolving the integral and replacing c, with
![c=\frac{(a-b)^2}4\implies\sqrt c=\frac2=\frac{b-a}2](https://img.qammunity.org/2021/formulas/mathematics/college/uj98zkf9d131xaol6ff5bmrj9eno4dhboc.png)
because
, gives
![I=\frac{b-a}2(\cos(2P)-\cos(2Q)-(P-Q))](https://img.qammunity.org/2021/formulas/mathematics/college/n70luav7teo1tb1f2xaxptxav1rtexs1wq.png)
Without knowing p and q explicitly, there's not much more to say.